Clinical characteristics for distinguishing between acute cardiogenic pulmonary edema and community-acquired pneumonia in elderly patients: a prospective observational study - Genki Inui; Katsuyuki Tomita; Masaharu Fukuki; Hirokazu Touge; Tomoyuki Ikeuchi; Ichiro Hisatome; Akira Yamasaki (Monaldi Archives for Chest Disease, 2023)
Heart failure and pneumonia are highly prevalent in elderly patients. We conducted a study to evaluate the differences in the patterns of symptoms, laboratory findings, and computed tomography (CT) results in elderly patients with acute cardiogenic pulmonary edema (ACPE) and community-acquired pneumonia (CAP). From January 1, 2015 to December 31, 2017, we studied 140 patients aged >75 years who were diagnosed with ACPE and CAP. Symptoms, laboratory findings, mean ostial pulmonary vein (PV) diameter and patterns on CT images were assessed. The primary measures of diagnostic accuracy were assessed using the positive likelihood ratio (LR+). The cutoff value of ostial PVs for differentiating patients with ACPE from CAP was evaluated using the receiver operating characteristic (ROC) analysis. Ninety-three patients with ACPE, 36 with CAP, and 11 with complicated ACPE/CAP were included. In patients with ACPE, edema (LR+ 5.4) was a moderate factor for rule-in, and a high brain natriuretic peptide level (LR+ 4.2) was weak. In patients with CAP, cough (LR+ 5.7) and leukocytosis (LR+ 5.2) were moderate factors for rule-in, while fever (LR+ 3.8) and a high C-reactive protein level (LR+ 4.8) were weak factors. The mean diameter of ostial PVs in patients with ACPE was significantly larger than that of patients with CAP (15.8± 1.8 mm vs 9.6±1.5 mm, p< 0.01). ROC analysis revealed that an ostial PV diameter cutoff of 12.5 mm was strong evidence for distinguishing ACPE from CAP with an area under the ROC curve of 0.99 and LR+ 36.0. In conclusion, as ACPE and CAP have similar symptoms and laboratory findings, dilated ostial PVs were useful in characterizing CT images to distinguish ACPE from CAP.